(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee retention is the most common problem of every organization. Retention is the most important aspect of every organization that can be improved by introducing variants of activities and programs to make them feel valuable and included. The best program to introduce in the organization to make the retention rate decrease is a wellness program that can track the needs of the employees. This can include stress management and making resources about mental health available. And add activities that will improve both physical and mental health. This step can lead to better performers and well-motivated employees that can lead to success. The result shows that the wellness practices observed by the respondents at Bestlink were mostly about health and lifestyle events, with 29 or 58%. The four (4) variables in the parts of what could be the impact of wellness programs on employee retention are all interpreted as extremely aware with their respective means of commitment (3.24), performance (3.35), mental health (3.24), and physical health (3.24). What are the problems encountered in wellness programs that get 13 or 26% out of 50? The study shows that most of the respondents were female and currently employed at Bestlink. Most of the respondents were non-teaching and had 1 - 2 years in service. It also reveals that wellness programs can improve employee retention in terms of commitment, performance, mental health, and physical health, and the common problem that may be encountered by the response of respondents is that it thinks that it can add expense to the organization. The researchers also suggested improving the wellness program by keeping the most needed of the employees and keeping the program aligned to make employees perform better and motivated. At the end of the study, the researchers provide recommendations, activities, and steps to enhance and improve employee retention in the organization by implementing wellness programs.